Topical anesthetic analgesic therapy using the combination of ropivacaine and dexmedetomidine: hyaluronic acid modified long-acting nanostructured lipid carriers containing a skin penetration enhancer - Yang Y; Qiu D; Liu Y; Chao L (Dove Medical Press, 2019)
Yongjian Yang, Dahai Qiu, Yajun Liu, Lei Chao Department of Anesthesiology, Jinan Central Hospital Affiliated to Shandong University, Ji’nan, Shandong Province 250013, People’s Republic of ChinaCorrespondence: Lei ChaoDepartment of Anesthesiology, Jinan Central Hospital Affiliated to Shandong University, No. 105 Jiefang Road, Ji’nan, Shandong Province 250013, People’s Republic of ChinaTel +86 05 318 569 5114Email leichaojncp@outlook.comPurpose: Hyaluronic acid-poly(ethylene glycol)-distearoyl phosphoethanolamine (HA-PEG-DSPE) modified and tocopheryl polyethylene glycol 1000 succinate (TPGS) contained nanostructured lipid carriers (NLCs) were prepared loading ropivacaine and dexmedetomidine to improve the topical anesthetic analgesic anesthesia efficiency.Methods: NLCs were prepared by the solvent diffusion method. The average particle size, zeta potential, release behavior, and cytotoxicity of the NLCs were tested. Ex vivo skin permeation was studied using a Franz diffusion cell mounted with depilated rat skin. Local anesthesia antinociceptive efficiency was evaluated by rat tail flick latency study in vivo.Results: NLCs have sizes of about 100 nm, with negative zeta potentials. All the NLCs formulations were found to be significantly less cytotoxic than free drugs at equivalent concentrations. The cumulative amount of drugs penetrated through rat skin from NLCs was 2.0–4.7 folds higher than that of the drugs solution. The in vivo anesthesia antinociception study displayed that NLCs showed stronger and longer anesthesia antinociceptive effect when compared with single drugs loaded NLCs and drugs solution even at a lower dosage of drugs.Conclusion: The results demonstrated that the HA modified, TPGS contained, dual drugs loaded NLCs could perform a synergistic effect and may reduce the amount of drugs, which can lower the toxicity of the system and at the meanwhile, increase the anesthesia antinociceptive efficiency.Keywords: topical anesthetic analgesic, skin penetration, hyaluronic acid, long-acting nanostructured lipid carriers, tocopheryl polyethylene glycol 1000 succinate